The Potential of Flos sophorae immaturus as a Pigment-Stabilizer to Improve the Monascus Pigments Preservation, Flavor Profiles, and Sensory Characteristic of Hong Qu Huangjiu - Yang, Yijin; Xia, Yongjun; Song, Xin; Mu, Zhiyong; Qiu, Huazhen; Tao, Leren; Ai, Lianzhong (Frontiers in Microbiology, 2021)
Hong Qu Huangjiu (HQW) is distinguished by its inclusion of Monascus pigments, which photosensitivity strongly affects the sensory quality of the wine. In this study, effects of Flos sophorae immaturus (FSI) on the stability of Monascus pigments, the flavor profiles and sensory characteristics of HQW were investigated. After sterilization, the addition of FSI increased the preservation rate of Monascus pigments in HQW the most by up to 93.20%, and the synergy of rutin and quercetin in FSI might be responsible. The total content of volatile flavor compounds in HQW increased significantly as the added amounts of FSI were increased, especially 3-methyl-1-butanol, 2-methyl-1-propanol and short-chain fatty acid ethyl esters (SCFAEE). Sensory evaluation and partial least-squares regression revealed that the concentration of FSI significantly affected the aroma characteristic of HQW, while had little effect on the mouthfeel. The addition of 0.9 mg/mL FSI yielded a satisfactory HQW with high scores in mouthfeel and aroma. In addition, the strong correlation between fruit-aroma, full-body and SCFAEE suggested that FSI might alter the aroma of HQW by enhancing the synthesis of SCFAEE. Summarily, treatment with FSI represented a new strategy for improving the stability of photosensitive pigments and thus adjusting the aroma of HQW or similar beverages.